Intragroup conflicts and efficiency of production group - Sidorenkov A.V. (Социальная психология и общество, 2017)
Analysis results of relationships of three levels of the conflict (interpersonal, microgroup and group) on two types (the job and subject ) with indicators of subjectively perceived performance and social effectiveness of small groups and informal subgroups are provided. On selection of 42 work groups (N=334 employees) it is established that performance efficiency of group according to the experts has inverse relation from all levels and types of the conflict, and by estimates of members of group — from two types of the microgroup conflict. The same type of effectiveness of informal subgroups on one indicator has inverse relation from the group conflict, and on another — from the interpersonal and microgroup conflict. Social effectiveness of group is connected with the interpersonal and group conflict, and informal subgroups are connected with the interpersonal and microgroup conflict. Levels and types of the conflict cause efficiency of group and subgroup not only separately, but also in a combination with each other. Six regression models, four of which display relationships at the same time of several levels and types of the conflict with performance effectiveness of group, and two — with social effectiveness of subgroup are revealed. Mediated and direct relationships of levels and types of the conflict with efficiency of group and subgroup are established.